Determinants Penerapan Computer-Assisted Audit Techniques (CAAT) dan Dampaknya terhadap Perceived Commercialisation Kantor Akuntan Publik - Zerry Sufanda; Emrinaldi Nur Dp; Nasrizal Nasrizal (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The development of accounting information systems has encouraged the use of information technology in various business fields, especially in the field of auditing such as the use of Computer-Assisted Audit Techniques (CAAT). The use of CAAT raises the question whether professional or organizational identity and perceived commercialization are the manifestations of the use of CAAT. This study aims to examine the effect of professional identity and organizational identity on the application of CAAT with the environment complexity of accounting information system as moderating. The results of this study prove that professional identity does not affect the application of CAAT implementation as well as the application of CAAT to perceived commercialization, while organizational identity influences the application of CAAT and professional identity and organizational identity influences the perceived commercialization when CAAT is applied. However, the environment complexity of accounting information system was able to strengthen the influence of CAAT implementation on perceived commercialization. This research contributes to the importance of professional responsibility and the application of CAAT to be a value added auditor performance.